Pangan Fungsional dari Ikan untuk Meningkatkan Kualitas Kesehatan di Era Pandemi Covid 19 Senyawa Fungsional dari Ikan dan Alga: Aplikasinya dalam Pangan - Tri Winarni Agustini (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Agustini TW. 2020. Fish-based functional food to improve health quality during pandemic covid 19 era functional compounds of fish and algae: applications in food. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The current COVID-19 pandemic requires us to maintain our immune system, one of which is by consuming nutritious foods. The high number of free radicals in the body can reduce the immune system. Antioxidants can prevent the overproduction of free radicals so that they can prevent damage to immune cells. Functional food is food or food ingredients containing bioactive compounds that can provide benefits beyond basic nutrition and provide health effects in the prevention of a disease. Fish and algae are a source of bioactive compounds with various bioactivity. Fish and algae functional compounds that have been utilized include proteins, peptides, polyunsaturated fatty acids (PUFAs), polysaccharides, pigments, and various active compounds that have antioxidant, antiviral and anti-inflammatory properties. Antioxidant nutrients commonly used are protein hydrolysate, β-carotene, chlorophyll, astaxanthin, fucoxanthin and phycocyanin as well as polyphenol group compounds. These functional compounds can be applied in functional food products in health care and prevention of disease. This paper briefly explain the functional compounds of fish and algae, their application to functional food products and future development trends.